2016
DOI: 10.1073/pnas.1523515113
|View full text |Cite
|
Sign up to set email alerts
|

A mutualistic symbiosis between a parasitic mite and a pathogenic virus undermines honey bee immunity and health

Abstract: Honey bee colony losses are triggered by interacting stress factors consistently associated with high loads of parasites and/or pathogens. A wealth of biotic and abiotic stressors are involved in the induction of this complex multifactorial syndrome, with the parasitic mite Varroa destructor and the associated deformed wing virus (DWV) apparently playing key roles. The mechanistic basis underpinning this association and the evolutionary implications remain largely obscure. Here we narrow this research gap by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
239
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 220 publications
(254 citation statements)
references
References 43 publications
12
239
1
2
Order By: Relevance
“…For example, expression of several AMP genes in honey bees was up-regulated following DWV infection of brood [37], while DWV infection, vectored by V . destructor , adversely affected humoral and cellular immune responses in bees [38]. However, Azzami et al [39] reported that the levels of AMPs were not elevated following artificial inoculation with ABPV.…”
Section: Discussionmentioning
confidence: 99%
“…For example, expression of several AMP genes in honey bees was up-regulated following DWV infection of brood [37], while DWV infection, vectored by V . destructor , adversely affected humoral and cellular immune responses in bees [38]. However, Azzami et al [39] reported that the levels of AMPs were not elevated following artificial inoculation with ABPV.…”
Section: Discussionmentioning
confidence: 99%
“…Varroa parasitism and associated viruses affect the honey bee immunity in complex ways (Di Prisco et al, 2016; Kuster et al, 2014) and a long-term suppression of some immune genes had previously been observed (Yang and Cox-Foster, 2005). Varroa parasitism decreases vitellogenin protein titers in the hemolymph of worker honey bees throughout adult life (Amdam et al, 2004a), which contrasts with our results.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenicity of DWV and the relationship between the virus, the mite, and the honey bee continue to be the focus of much research in honey bee pathology (Di Prisco et al, 2016;Möckel et al, 2010;Ryabov et al, 2014). The known DWV strains (Type A, B, and C), and recombinants thereof, may be linked to differences in DWV virulence in honey bee colonies (Martin et al, 2012;McMahon et al, 2016;Ryabov et al, 2014;Zioni et al, 2011), however, there is no evidence that strains may be specifically linked to wing deformities on bees, rather it appears that viral loads of DWV play a significant role in the expression of this phenotype in honey bees (Brettell et al, 2017).…”
Section: Floral Resources Have Been Identified As a Potential Contactmentioning
confidence: 99%